Displaying overt recipiency: reactive tokens in Mandarin task-oriented conversation - Xu, Jun (2009)
This thesis examines the interconnection between the linguistic forms of reactive tokens and their associated conversational actions in Mandarin conversation. It aims to show how reactive tokens are produced and interpreted by participants themselves as the display of an awareness of being a recipient in longer sequences. The central argument of the thesis is that participants display overt recipiency through variation and selection of reactive tokens in longer sequences in Mandarin conversation.